PEMETAAN PENDUDUK DAN EKONOMI RUMAH TANGGA DI KENAGARIAN CANDUANG KOTO LAWEH TAHUN 2020 - IDRIS AFANDY; Yurni Suasti (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The purpose of this research; 1) the age characteristics of a gender-based population. 2) Knowing the level of education of the gender-based population. 3) Knowing the type of work on household economic activities. 4) Knowing work income towards household economic activities.5)Determine the outpouring of working hours of the population on household economic activities based on gender. The data used in this study are primary data obtained from interviews with a combination of questionnaires. The number of samples used was 92 kk, with a proportional random sampling method. The analysis technique used in this study is p = f / n. In getting the results of the characteristics of age, education level, type of work, work income and hours of work hours, the results showed 1) the characteristics of age are dominated by male productive age 97 people (47%) female productive age 93 (54%) 2) level education is dominated by male primary education 101 people (49%) female basic education 70 people (41%) 3) types of work are dominated by male workers / farmers 82 people (22%) female irt 47 people (27%) 4 ) The level of income is dominated by middle income men 48 people (23%) low income women 26 people (15%) 5) Expended working hours are dominated by high working hours men 75 people (36%) women high working hours 41 people (24%).